Design of BMT Al-HUDA UNS Savings Information System - Mudhi Handayani, Eko; Saptono, Ristu; Respatiwulan, Respatiwulan (oneamrd (One a Mllions Dreams Corporation), 2024)
This study aims to design a BMT Savings Information System (Baitul Maal wat Tamwil) at Al-HUDA, Sebelas Maret State University (UNS) Surakarta to improve the efficiency of member fund management. This system is designed to facilitate the process of deposits, withdrawals, transaction recording, and real-time web-based financial reporting. The system development method uses the Waterfall approach, starting from needs analysis, design, implementation, to testing. The results of the study show that this system is able to reduce manual errors, speed up the transaction process, and improve BMT financial accountability. With this system, it is expected to support the digitalization of sharia financial services in the campus environment and provide convenience for members in managing savings.